The Effect of Employee Well-Being and Digital Social Capital on Employee Retention with Resilience as A Mediator - Fatwa Zuhaena; Ratna Pujiastuti; Harsuti (Attractive : Innovative Education Journal, 2025)
Islamic microfinance institutions operate in an increasingly challenging environment characterized by competition, digitalization, and limited internal resources, making employee retention a strategic concern for organizational sustainability. This study examines the effects of employee well-being and digital social capital on employee retention, with resilience serving as a mediating variable, among employees of Baitul Maal wat Tamwil (BMT) in the former Banyumas Residency. The research framework integrates Job Demands–Resources (JD-R) Theory and Conservation of Resources (COR) Theory to explain the relationships among job resources, personal resources, and retention decisions. A quantitative survey was conducted involving 190 BMT employees with a minimum tenure of one year. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The findings reveal that employee well-being and digital social capital positively and significantly influence both employee retention and resilience. However, resilience was found to have a negative effect on employee retention. Furthermore, resilience mediates the relationships between employee well-being and retention, as well as between digital social capital and retention. These results suggest that in Islamic microfinance institutions characterized by high work demands and limited career development opportunities, highly resilient employees may be more prepared to pursue career mobility. The study highlights the importance of balancing the development of individual resources with adequate organizational support to enhance employee retention and ensure long-term organizational sustainability